Requirement of estrogen receptor alpha DNA-binding domain for HPV oncogene-induced cervical carcinogenesis in mice - Son, Jieun (Oxford University Press, 2014)
Cervical cancer is caused by human papillomavirus (HPV) in collaboration with other non-viral factors. The uterine cervix is hormone responsive and female hormones have been implicated in the pathogenesis of the disease. HPV transgenic mice expressing HPV16 oncogenes E6 (K14E6) and/or E7 (K14E7) have been employed to study a mechanism of estrogen and estrogen receptor α (ERα) in cervical carcinogenesis. A chronic exposure to physiological levels of exogenous estrogen leads to cervical cancer in the HPV transgenic mice, which depends on ERα. The receptor is composed of multiple functional domains including a DNA-binding domain (DBD), which mediates its binding to estrogen-responsive elements (EREs) on target genes. A transcriptional control of genes by ERα is mediated by either DBD-dependent (classical) or DBD-independent (non-classical) pathway. Although molecular mechanisms of ERα in cancer have been characterized extensively, studies investigating importance of each pathway for carcinogenesis are scarce. In this study, we employ knock-in mice expressing an ERα DBD mutant (E207A/G208A) that is defective specifically for ERE binding. We demonstrate that the ERα DBD mutant fails to support estrogen-induced epithelial cell proliferation and carcinogenesis in the cervix of K14E7 transgenic mice. We also demonstrate that cervical diseases are absent in K14E7 mice when one ERα DBD mutant allele and one wild-type allele are present. We conclude that the ERα classical pathway is required for cervical carcinogenesis in a mouse model.